Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

If $\alpha \not= \beta$, and $$ a\tan \alpha+b\tan\beta=(a+b)\tan\frac{\alpha+\beta}{2}$$ then can we prove that $\frac{\cos\alpha}{\cos\beta}=\frac{a}{b}$?

Seems like I am stuck on this one.

share|cite|improve this question
This is not true. $\alpha = 0$, $\beta = 2\pi$. Are there any restrictions? Like maybe they are acute? – Aryabhata Feb 29 '12 at 6:35
I wonder if it might help to recall that $\tan((\alpha+\beta)/2)=(\sin\alpha+\sin\beta)/(\cos\alpha+\cos\beta)$? – Michael Hardy Feb 29 '12 at 15:12
up vote 2 down vote accepted

This is true if we assume $\displaystyle \sin\left(\frac{\alpha -\beta}{2}\right) \neq 0$ and $\displaystyle b \neq 0$.

Let $\displaystyle \frac{a}{b} = c$

Rewrite your equation as

$$c\tan \alpha + \tan \beta = (c+1)\tan(\frac{\alpha+\beta}{2})$$

$$ c\left(\tan \alpha - \tan\left(\frac{\alpha+\beta}{2}\right)\right) = \tan\left(\frac{\alpha+\beta}{2}\right) - \tan \beta$$

Using $\displaystyle \tan x + \tan y = \frac{\sin(x+y)}{\cos x \cos y}$ we get

$$ c \cdot \frac{\sin\left(\frac{\alpha-\beta}{2}\right)}{\cos \alpha \cos \left(\frac{\alpha+\beta}{2}\right)} =\frac{\sin\left(\frac{\alpha-\beta}{2}\right)}{\cos \beta \cos \left(\frac{\alpha+\beta}{2}\right)}$$

and so

$$ \frac{\cos \alpha}{\cos \beta} = c = \frac{a}{b}$$

share|cite|improve this answer
$\displaystyle\tan(x)+\tan(y)=\frac{\sin(x+y)}{\cos(x)\cos(y)}$ makes this a lot simpler. (+1) – robjohn Feb 29 '12 at 13:09

enter image description here

Sorry for bad drawing. The drawing is equal to the question.



$x=a\tan \alpha$

$y=b\tan \beta$

Focus on EAD triangle.

$\tan (m(EAD))=\frac{x+y}{a+b}=\frac{a\tan \alpha+b\tan \beta}{a+b}=\frac{(a+b)\tan \frac{(\alpha+\beta)}{2}}{a+b}=\tan \frac{(\alpha+\beta)}{2}$



Let's calculate the angles: $m(BAD)$ and $m(ABD)$ and $m(ADB)$





if so ABD triangle is an isosceles triangle Thus $AB=BD$

$AB=\frac{a}{\cos \alpha}$

$BD=\frac{b}{\cos \beta}$

$\frac{a}{\cos \alpha}=\frac{b}{\cos \beta}$

$\frac{\cos \alpha}{\cos \beta}=\frac{a}{b}$

share|cite|improve this answer
I'd been looking for the picture proof, and you beat me to it! :) But ... Isn't the similarity stuff irrelevant? The key is that $\triangle ABD$ is isosceles (say, with leg $r$), so that $a = r\cos\alpha$ and $b = r\cos\beta$ ... and we're done, right? – Blue Feb 29 '12 at 14:24
(Missed the comment-editing time window.) That $\angle HAC = (\alpha+\beta)/2$ simply restates the assumed relation, since $(a+b)\tan(\angle HAC) = x+y = a\tan\alpha+b\tan\beta$. There's no need to derive this angle's measure; we're given it. – Blue Feb 29 '12 at 14:33
If We do not have the relation $a\tan \alpha+b\tan \beta=(a+b)\tan \frac{(\alpha+\beta)}{2}$ in question, We cannot say $m(HAC)=\frac{(\alpha+\beta)}{2}$ – Mathlover Feb 29 '12 at 14:54
Right, and you used the relation in your computation of $k$. I'm just saying that the relation is immediately observable in your clever diagram: In $\triangle DAE$, clearly $\tan\angle DAE = (x+y)/(a+b)$. We're told that $(\alpha+\beta)/2$ matches this tangent value, so there's nothing elaborate to prove here. Thales is certainly overkill. – Blue Feb 29 '12 at 15:46
I saw what you mean. you are correct.Blue triangle is enough to proof. Thanks in advice. – Mathlover Feb 29 '12 at 19:28

Noting that $$ \begin{align} \tan\left(\frac{\alpha+\beta}{2}\right) &=\frac{\sin(\alpha+\beta)}{1+\cos(\alpha+\beta)}\\ &=\frac{\sin(\alpha)\cos(\beta)+\cos(\alpha)\sin(\beta)}{1+\cos(\alpha)\cos(\beta)-\sin(\alpha)\sin(\beta)}\\ &=\frac{\tan(\alpha)+\tan(\beta)}{1+\sec(\alpha)\sec(\beta)-\tan(\alpha)\tan(\beta)}\tag{1} \end{align} $$ yields $$ \begin{align} \tan\left(\frac{\alpha+\beta}{2}\right)-\tan(\beta) &=\frac{\tan(\alpha)+\tan(\beta)}{1+\sec(\alpha)\sec(\beta)-\tan(\alpha)\tan(\beta)}-\tan(\beta)\\ &=\frac{\tan(\alpha)-\sec(\alpha)\sec(\beta)\tan(\beta)+\tan(\alpha)\tan^2(\beta)}{1+\sec(\alpha)\sec(\beta)-\tan(\alpha)\tan(\beta)}\\ &=\frac{\tan(\alpha)\sec^2(\beta)-\sec(\alpha)\sec^2(\beta)\sin(\beta)}{1+\sec(\alpha)\sec(\beta)-\tan(\alpha)\tan(\beta)}\\ &=\frac{\tan(\alpha)-\sec(\alpha)\sin(\beta)}{\cos^2(\beta)+\sec(\alpha)\cos(\beta)-\tan(\alpha)\cos(\beta)\sin(\beta)}\\ &=\frac{\sec(\alpha)(\sin(\alpha)-\sin(\beta))}{\cos(\beta)\sec(\alpha)(\cos(\alpha)\cos(\beta)+1-\sin(\alpha)\sin(\beta))}\\ &=\frac{\sin(\alpha)-\sin(\beta)}{\cos(\beta)(\cos(\alpha+\beta)+1)}\tag{2} \end{align} $$ Symmetry and negation yields $$ \tan(\alpha)-\tan\left(\frac{\alpha+\beta}{2}\right)=\frac{\sin(\alpha)-\sin(\beta)}{\cos(\alpha)(\cos(\alpha+\beta)+1)}\tag{3} $$ Dividing $(2)$ by $(3)$ yields $$ \frac{\tan\left(\frac{\alpha+\beta}{2}\right)-\tan(\beta)}{\tan(\alpha)-\tan\left(\frac{\alpha+\beta}{2}\right)}=\frac{\cos(\alpha)}{\cos(\beta)}\tag{4} $$ Back to the original equation: $$ a\tan(\alpha)+b\tan(\beta)=(a+b)\tan\left(\frac{\alpha+\beta}{2}\right) $$ Dividing both sides by $b$: $$ \frac{a}{b}\tan(\alpha)+\tan(\beta)=\left(\frac{a}{b}+1\right)\tan\left(\frac{\alpha+\beta}{2}\right) $$ Collecting $\frac{a}{b}$ on the left: $$ \frac{a}{b}\left(\tan(\alpha)-\tan\left(\frac{\alpha+\beta}{2}\right)\right)=\tan\left(\frac{\alpha+\beta}{2}\right)-\tan(\beta) $$ Thus, by $(4)$, $$ \frac{a}{b}=\frac{\tan\left(\frac{\alpha+\beta}{2}\right)-\tan(\beta)}{\tan(\alpha)-\tan\left(\frac{\alpha+\beta}{2}\right)}=\frac{\cos(\alpha)}{\cos(\beta)} $$ as requested.

share|cite|improve this answer

Did you try applying some identities? $\tan\theta=\frac{\sin\theta}{\cos\theta}$ if $\cos\theta\neq0$. $\tan(\alpha+\beta)=\frac{\tan\alpha+\tan\beta}{1-\tan\alpha\tan\beta}$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.